Ageing by feet? Regional migration, neighbourhood choice and local demographic change in German cities - Uwe Neumann (European Regional Science Association (ERSA), 2015)
In the literature on the economics of demographic change so far the regional and neighbourhood-level consequences were out of the main focus. Yet, regional migration accentuates diversity in the progress of ageing. In fact, while households are known to ?vote with their feet? when they choose a residential location, neighbourhood populations may experience ?ageing by feet? as an outcome of a multitude of individual location decisions. This paper examines at what pace demographic change proceeds at the neighbourhood level in an ageing region and to what extent regional migration and neighbourhood choice during the past two decades reinforced or changed patterns of residential segregation among urban neighbourhoods. German cities differ from those in many other highly developed countries in that their population has stagnated or even begun to decline during the past decades. Apart from Eastern Germany, due to decades of net migration to more prosperous regions, the old-industrialised Ruhr in North Rhine-Westphalia is one of the German regions, which have already been affected by a severe loss in population and fundamental population change over the past decades. Drawing on municipal data at the sub-city level and microdata from a representative survey, this paper examines how change in the composition of neighbourhood populations relates to regional migration. The first step of the analysis focuses on the pace of neighbourhood-level demographic change during the period from 1998 to 2008. The second step examines household preferences relating to residential locations in the Ruhr, based on microdata from a representative survey carried out in 2010. The identification strategy is adopted from the recent literature on the microeconomics of discrete choice. In the Ruhr region, over the past decades out-migration and demographic ageing coincided with changes in intra-regional migration. After several decades of suburbanisation, in the 1990s net migration to suburban municipalities came to a halt. The micro-level analysis finds that among household preference apparently the desire for centrality took over from preference of low-density surroundings, which had dominated for decades. Within urban areas, migration now concentrates more on selected neighbourhoods in close vicinity to the city centres. In other neighbourhoods, due to low fertility and a comparatively low influx of young inhabitants, the average age has begun to increase. It is a specific characteristic of the Ruhr, which is an amalgam of neighbouring cities, to be less densely populated than other large urban agglomerations in Germany. Lower overall density here combines with a comparatively less pronounced agglomeration of working-age adults in central areas. As a whole, local demographic change implies new challenges for urban policy in many neighbourhoods, both in those not providing the characteristics favoured by most mobile households and in those with a high influx.
Keywords: C21; C25; O18; R23; 330; demographic change; neighbourhood choice; regional migration; segregation